The Impact Of The Loss Of The Basement Seen From The Side Of The Principle Of Social Function - Annastasya Saputri, Nindya; Sulistiyono, Adi; Hermawan, Sapto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The basement is a building that is below ground level; currently, with the increasing need for land to be built because of the increasing population, a basement will be built to be used as an underground building. The MRT, basement parking lots, and shops are examples of buildings currently being built. The building must follow the social function regulated in the UUPA so that it can be enjoyed and used by all parties and communities so that what is achieved for the greatest prosperity of the people has been achieved properly. However, it does not rule out the possibility of damage or loss of the underground, causing a negative social impact on the damage and loss of the basement. This research uses a type of normative research by analyzing using a statutory approach and a conceptual approach. The source of legal materials is the UUPA, the 1945 Constitution, and Government Regulation 18 of 2021 which regulates a few concerning using basements. The goal is to be able to answer all the problems that will be raised in the research in this article.